Interinstitutional Coordination in the Management of Natural Emergencies - Bozmarova, Adela (Research Papers, 2022)
The relevance of this material is aimed at improving inter-institutional coordination in emergency management. This requires an in-depth and structured analysis of the challenges facing emergency management, in the context of coordination between institutions in this sector in the Republic of Bulgaria.The object of the present study is inter-institutional coordination. The subject of the research is the improvement of the inter-institutional coordination in emergency management.The main goal of the study is to propose measures to improve inter-institutional coordination in the management of natural emergencies.{~~The thesis that defends~>The thesis that this study defends~~} the current study is that the lack of effective and structured inter-institutional coordination in emergency management leads to the negative consequences of the emergency and complicates the process of its management.
Keywords: Emergency management; Inter-institutional coordination; Landslide